Using Lawsuits-Based YouTube Videos to Reinforce Students’ English Speaking Fluency: The Case of Business Law Students at Bechar University (مجلة الواحات للبحوث والدراسات, 2023)
Abstract: YouTube is a crucial online audio-visual resource that is used by a multitude of language educational endeavours to teach English and spur learner autonomy. Thus, the current research sought to examine the impact of using Lawsuits-Based YouTube Videos (LBYV) on reinforcing business law students’ English speaking fluency. For this purpose, the researcher employed a pre-experimental—one-group pretest-posttest design. The participants were first-year Master students (30) in the Department of Law, Tahri Mohamed University (Algeria). To collect data, speaking fluency pre-/ post-assessment was administered at the beginning and at the end of the treatment during ten sessions of Legal English course. Descriptive statistics and paired samples t-test were used to analyse quantitative data via SPSS 26. The findings revealed that the implementation of LBYV brought about statistically significant difference between pre-test mean scores (7) and post-test mean scores (10.5) in favour of post-test (t (29) = 16.025; p= 0.00 < 0.05). Keywords: Business Law Students, Lawsuits-Based YouTube Videos, Legal English, Speaking Fluency.